Analisis Proses Pengolahan Air Minum Pada Perusahaan Daerah Air Minum Desa Cahaya Negeri - Yoga Sarwenda; Oktarianita Oktarianita; M Amin; Nopia Wati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Clean water treatment for the needs of the people of Bengkulu is carried out by several agencies, one of which is managed by The City-Owned Water Company PDAM of Cahaya Negeri Village which is a business entity owned by the local government. This type of study was a qualitative research using interview guidelines and conducting observations. There were 3 informants in this study, namely, the head of the processing unit, the head of the laboratory and the processing operator. The research was conducted in Janaury 2021. The results of the study indicate that PDAM Cahaya Negeri was running well, the processing units were also complete, from maintenance of intake, type of intake pump, coagulation equipment and coagulant material, flocculation building is still very good, sedimentation process is also good, filtration material with silica sand is also appropriate, because the absorption of silica sand is good, and the last is disinfection, using chlorinated material is good for killing bacteria in treated water. The processed water has also met the standard of the Minister of Health Regulation No. 32 of 2017, concerning clean water standards. However, rainfall greatly affects the condition of raw water quality for processing and moreover the local power plant which often shuts down is an obstacle for PDAM CahayaNegeri to carry out processing. It is expected that the PDAM of CahayaNegeri can maintain its achievements and find solutions to its obstacles, in order to meet the need for clean water.